Posterior Cerebral Artery Aneurysm with Posteromedial Choroidal Artery-P3 Segment Anastomosis - Majoie, C.B. (Centauro S.r.l., 2009)
We describe the case of a patient with an aneurysm of the P2 segment of the PCA with a persistent anastomosis between the posteromedial choroidal artery and the P3 segment of the posterior cerebral artery.